Genetic recording of pancreatic beta cell proliferation - Huan Zhao; Hui Chen; Zhixin Kang; Xiuzhen Huang; Jingting Zhu; Zixin Liu; Xiuxiu Liu; Ximeng Han; Jie Lu; Bin Zhou (Proceedings of the National Academy of Sciences, 2026)
Pancreatic beta cell generation and proliferation primarily rely on the self renewal of preexisting beta cells, making precise quantification of beta cell proliferation essential for understanding pancreatic homeostasis and pathogenesis. However, previous methods had limitations and were unable to trace beta cell proliferation in vivo over extended periods. Here, we developed beta cell ProTracer, a genetic system that uses dual recombinase technology to enable continuous and cell type-specific recording of beta cell proliferation in mice. The beta cell ProTracer system allows for the quantification of the proliferation rate of adult pancreatic beta cells during homeostasis and in response to injury or drug treatment. Clonal analysis of the proliferated beta cell population reveals a uniform proliferative capacity among these cells. Our findings enhance the understanding of beta cell proliferation dynamics in homeostasis, repair, and regeneration.